DAMPAK STRUKTUR MODAL TERHADAP KINERJA KEUANGAN PERUSAHAAN KELUARGA TERBUKA: STUDI KASUS PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - James Gan; Johny Budiman; Hesnianti (MANAJEMEN DEWANTARA, 2026)
This study examines the impact of capital structure on the financial performance of family-owned firms in Indonesia. In addition, it explores the moderating role of ownership concentration. The data were obtained from family firms listed on the Indonesia Stock Exchange (IDX) for the period 2019–2024 and analyzed using panel data regression with a fixed effects model. Capital structure is measured using the ratios of short-term debt, long-term debt, and total debt to total assets, while financial performance is assessed using ROA and ROE. The results indicate that both short-term and long-term debt have a significant negative effect on ROA and ROE, whereas total debt shows a significantly positive effect on both performance indicators. Ownership concentration moderates these relationships, with effects that either strengthen or weaken the influence of debt depending on the type. Control variables such as firm size and age show no significant impact on performance, while sales growth positively affects ROA only. These findings highlight the importance of maintaining a balanced capital structure and the strategic role of concentrated ownership in enhancing the effectiveness of financial decision-making.